Guessing Games: Enhancing English Speaking Skills in Secondary School: Meningkatkan Kemampuan Berbicara Bahasa Inggris melalui Permainan Tebak Kata: Studi Kuantitatif di Sekolah Menengah - Wega Dhea Agnesia; Yuli Astutik (Academia Open, 2023)
This study investigates the effectiveness of incorporating guessing games as an English learning strategy, specifically focusing on improving students' speaking skills. Many students face challenges in speaking English due to perceiving it as a difficult language to learn, resulting in a lack of mastery. To address this issue, a quantitative approach was employed, involving a sample of 33 students from an eighth-grade class at SMPN 2 Gempol. Data collection included a pre-test and post-test, with the analysis conducted using the T-paired Test. The results revealed that the t-test value (16.369) exceeded the critical t-table value (2.036). Thus, the null hypothesis (H0) was rejected, and the alternative hypothesis (H1) was accepted, indicating a significant positive impact of guessing games on English speaking skills. The findings suggest that teachers can effectively utilize guessing games as an engaging instructional tool to enhance students' proficiency in spoken English. Highlights: Utilizing guessing games as an instructional strategy for English learning. Assessing the effectiveness of guessing games on students' speaking skills. Significant positive impact of guessing games on English speaking proficiency. Keywords: Guessing games, English learning, Speaking skills, Quantitative method, Secondary school